Passenger Satisfaction Evaluation of Public Transportation in Istanbul by Using Fuzzy Quality Function Deployment Methodology - Bilisik, Ozge Nalan; Seker, Sukran; Aydin, Nezir; Gungor, Nihan; Baracli, Hayri (SPRINGER HEIDELBERG, 2019)
Quality Function Deployment (QFD) is known as a planning process and methodology that helps companies for listening voice of customers. This process assists company to produce new or improve current products and services according to voice of customers. QFD provides this by transforming voice of customers into the technical language of the company. The aim of this study is to increase service quality and passenger satisfaction by listening voice of passengers, determining their requirements, and integrating these requirements into public transportation services properly. On the other hand, the nature of uncertainty and subjectivity in service delivery processes makes difficult employing QFD effectively. Thus, fuzzy QFD methodology is applied to evaluate public transportation firms in Istanbul including BRT, IETT, Otobus Inc., and Private Busses. At the end of the study, conclusions and discussions are drawn concerning the requirements of passengers to reduce the complaints and improve public transportation services quality.
Keywords: Fuzzy QFD; Public transportation; Passenger requirements; Passenger satisfaction; LINEAR-REGRESSION ANALYSIS; CUSTOMER SATISFACTION; SERVICE QUALITY; IMPROVEMENT; QFD; Science & Technology - Other Topics